1988
DOI: 10.1159/000116225
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus in Kearns-Sayre Syndrome

Abstract: A 20-year-old woman with Kearns-Sayre syndrome (KSS) suddenly experienced two episodes of diabetic coma. She was studied to determine whether diabetes mellitus (DM) resulted from insulin resistance or from an insulin secretion abnormality, using the euglycemic glucose clamp technique and the glucagon tolerance test. She had a deficiency of insulin secretion from beta cells. It is important to recognize in practice the onset of DM in patients with mitochondrial myopathy. We would suggest that a genetic linkage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…In addition, defective insulin secretion and regional adiposity may be more important than skeletal muscle mitochondrial function in the development of glucose intolerance with aging (5), raising the possibility that the link between mitochondrial dysfunction and insulin resistance is tenuous. Consistent with this idea, human mitochondrial mutations cause myopathy and diabetes that is due to insulin secretory failure, usually in the absence of insulin resistance (3,6,41).…”
Section: Discussionmentioning
confidence: 79%
“…In addition, defective insulin secretion and regional adiposity may be more important than skeletal muscle mitochondrial function in the development of glucose intolerance with aging (5), raising the possibility that the link between mitochondrial dysfunction and insulin resistance is tenuous. Consistent with this idea, human mitochondrial mutations cause myopathy and diabetes that is due to insulin secretory failure, usually in the absence of insulin resistance (3,6,41).…”
Section: Discussionmentioning
confidence: 79%
“…Can an increase in the incidence of insulin-dependent diabetes mellitus (IDDM) be on the basis of environmental exposure or other factors involving the mitochondrial genome? (147)(148)(149). The earlier the onset of mitochondrial myopathy in these conditions, the more frequent was its association with IDDM (150).…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Kadowaki et al [9] and Awata et al [10] demonstrated a significant reduction of maximal insulin secretory capacity and early secretion response of insulin to glucose administration in diabetic patients with the 3243 bp mutation. Several additional reports demonstrated reduced insulin secretion in diabetes with other mitochondrial diseases, such as CPEO and KSS [22,25]. In contrast, Van den Ouweland et al [5] and Sue et al [13] showed substantial rises in insulin concentrations in several diabetic subjects with the mutation.…”
Section: Discussionmentioning
confidence: 95%
“…Several lines of evidence suggest that CPEO including Kearns-Sayre syndrome (KSS) is frequently associated with IDDM [20][21][22]. Recent reports also suggest that the MELAS-related mitochondrial gene mutation of tRNA I"zu(uum (3243) associates with maternally inherited diabetes and with neurosensory deafness [5,6,[9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation